Aerobic Photooxidative Synthesis of Secondary Aldimines from Benzylamines by Using Methylene Blue - Okada, Akifumi; Yuasa, Hiroki; Fujiya, Akitoshi; Tada, Norihiro; Miura, Tsuyoshi; Itoh, Akichika (Synlett, 2015)
We have developed a concise oxidative coupling of primary benzylamines to yield secondary aldimines catalyzed by methylene blue by using molecular oxygen as the oxidant in the presence of visible-light irradiation from fluorescent lamps.
Keywords: aerobic; methylene blue; photooxidation; singlet oxygen; primary amine; imine